Investigating the effect of vandetanib and celecoxib combination on angiogenesis - Abdul Qadir, MPhil; Danish Abdus Samad, FCPS; Mahayrookh Asif, PhD; Muhammad Mujtaba Ali, PhD; Syeda Zain, MPhil (Journal of Taibah University Medical Sciences, 2023)
المخلص: أهداف البحث: يلعب تولد الأوعية دورا مهما في مختلف الحالات الفسيولوجية والمرضية. إنه ضروري لنمو الورم ورم خبيث. الهدف من هذه الدراسة هو تقييم تأثير تركيبة فانديتانيب وسيليكوكسيب على تكوين الأنبوب الوعائي وتأثيره على الجينات المولدة للأوعية (م.م.ب -2 و م.م.ب -9) باستخدام نموذج مختبري للإنسان. الخلايا البطانية للوريد السري. طرق البحث: تم استنبات الخلايا البطانية للوريد السري البشري والتحقق منها عن طريق قياس التدفق الخلوي. عولجت الخلايا البطانية في الوريد السري البشري بفانديتانيب وسيليكوكسيب ومزيج من العقارين ، وتم تحديد قابلية بقاء الخلية وموت الخلايا المبرمج باستخدام مقايسة م.ت.ت وقياس التدفق الخلوي. تم تحليل عملية تكوين الأوعية باستخدام اختبار تكوين الأنبوب، وتم تحديد التأثير على الجينات المولدة للأوعية باستخدام النسخ العكسي لتفاعل البلمرة المتسلسل الكمي في الوقت الحقيقي. النتائج: كانت الخلايا البطانية للوريد السري البشري موجبة لـ سي.دي-144 وسلبية لـ سي.دي-14. أدى فانديتانيب وسيليكوكسيب وتركيبهما إلى تثبيط بقاء الخلايا البطانية للوريد السري البشري بطريقة تعتمد على الجرعة. كان معدل موت الخلايا المبرمج 13.1٪، 9٪ و 23.7٪، عند العلاج بـ فانديتانيب، سيليكوكسيب، أو مزيج من كلا العقارين. منع فانديتانيب تشكيل الأنبوب بنسبة 43.7٪ ، والسيليكوكسيب بنسبة 21٪، ومزيجهم بنسبة 77.3٪ على التوالي. النسخ العكسي من تفاعل البوليميراز المتسلسل الكمي في الوقت الحقيقي. أظهر أن كلا من فاندتانيب وسيليكوكسيب يقللان من مستويات التعبير عن م.م.ب -2 و م.م.ب -9، وأظهر الجمع بينهما مستوى أعلى من الانخفاض في التعبير المستوى الذي وجد أنه ذو دلالة إحصائية. الاستنتاجات: سيليكوكسيب يعزز تأثير فانديتانيب في تثبيط تكوين الأوعية في المختبر، وقد أظهر الجمع بينهما مستويات أعلى من التثبيط مقارنة باستخدام فانديتانيب وحده. Abstract: Objective: Angiogenesis plays an important role in various physiological and pathological conditions and is essential for tumor growth and metastasis. The aim of this study was to evaluate the effect of a combination of vandetanib and celecoxib on angiogenic tube formation and its effect on angiogenic genes (MMP-2 and MMP-9) using an in vitro model of human umbilical vein endothelial cells (HUVECs). Methods: HUVECs were cultured and verified by flow cytometry. HUVECs were then treated with vandetanib, celecoxib, and the combination of both drugs. Then, we investigated cell viability and cell apoptosis by MTT assays and flow cytometry. The process of angiogenesis was analyzed by tube formation assays, and the effect on angiogenic genes was determined by RT-qPCR. Results: HUVECs were positive for CD144 and negative for CD14. Vandetanib, celecoxib, and their combination inhibited HUVEC viability in a dose-dependent manner (p < 0.001). The rate of apoptosis was 13.1%, 9%, and 23.7% (p < 0.001) when treated with vandetanib, celecoxib, or the combination of both drugs, respectively. Vandetanib inhibited tube formation by 43.7%, celecoxib by 21%, and their combination by 77.3% (p < 0.001), respectively. RT-qPCR revealed that both vandetanib and celecoxib reduced the expression levels of MMP-2 and MMP-9, and their combination resulted in an even greater extent of reduction in expression levels (p < 0.001). Conclusion: Celecoxib enhanced the effect of vandetanib in inhibiting in vitro angiogenesis and the combination of these two drugs led to even greater extents of inhibition than vandetanib alone.